The Effective Concentration of the Crude Extract of Mentha picata and Eucalyptus against the Growth of Fusarium oxysporum - Fradi, Ahmed Jassim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
This research aims to evaluate The effect of plant extract concentration as antifungal. Fusarium fungus was isolated from the eggplant and cucumber plants that infested them. These were tested for concentrations of the pathogenic fungus Fusarium oxysporum according to the food poisoning method. The inhibition rate was calculated by measuring the diameter of the colony compared to the control. The results showed that in the crude extract of Eucalyptus at a concentration of 12%, the percentage of growth inhibition was 100% on Fusarium oxysporum, compared to the crude extract of Mentha spicata where the percentage of inhibition was 80.11%. At the same concentration, and the percentage of inhibition of Eucalyptus extract At concentrations 3,6, and 9% ranged between (35.33-79.55) while the inhibition of Mentha spicata extract ranged between (17.20 - 80.11 ) at the same concentrations.